Minipuberty assessment in newborns with hypoxic ischemic encephalopathy treated with therapeutic hypothermia: a single-center case–control study - Lanciotti, Lucia; Sica, Rossella; Penta, Laura; Parisi, Francesca; Argentiero, Alberto; Radicioni, Maurizio; Di Cara, Giuseppe; Di Genova, Francesca; Verrotti, Alberto; Troiani, Stefania; Esposito, Susanna Maria Roberta (Frontiers in Pediatrics, 2023)
The aim of our single center case-control study was to evaluate if minipuberty occurs in patients with hypoxic ischemic encephalopathy (HIE) who underwent Therapeutic hypothermia (TH) by confronting the values of Luteinizing hormone (LH) and Follicle-stimulating hormone (FSH) and the values of testosterone in males and estradiol in females between newborns with HIE and subsequent TH and healthy controls. We enrolled 40 patients (age: 56 to 179 days; 23 males), 20 of which met the inclusion criteria for the case group and have undergone TH. A blood sample was taken from each patient around 10 weeks of age to evaluate FSH and LH from serum samples of all patients, 17-beta estradiol (E2) and testosterone respectively from serum samples of female and male patients. . Minipuberty occurred in the case group with no significant differences from the control group and with hormonal serum levels comparable to healthy infants of the control group (FSH 4.14 mUI/mL ± 5.81 sd vs 3.45 mUI/mL ± 3.48 sd; LH 1.41 mUI/mL ±1.29 sd vs 2.04 mUI/mL ±1.76 sd; testosterone in males 0.79 ng/mL ± 0.43 sd vs 0.56 ng/mL ± 0.43 sd; 17-beta estradiol in females 28.90 pg/mL ± 16.71 sd vs 23.66 pg/mL ± 21.29 sd). The results of the present study might open to further research and to evaluate more possible advantages of TH.